'Localness' is good for business? An intellectual capital-based perspective in the Italian food industry. Issue 2 (21st October 2008) - Massa, Silvia; Testa, Stefania
This paper investigates the ability of local food producers to exploit the elements of regional Intellectual Capital (IC) embedded in local food systems in order to gain a competitive advantage. This paper analyses how an appropriate use of regional IC, combined with organisational IC, can increase firms' competitive advantage. The focus is on the interaction between regional IC and organisational IC so as to reach a higher collective yield of competitiveness, that is, an IC multiplier effect. The existence of a feedback effect is also examined, that is, whether the success of firms taking advantage of regional IC contributes to the success of the local area, thus initiating a virtuous cycle.